From rural citizenship to the rural citizen: Farming, dementia and networks of care. (October 2018) - Kelly, Claire; Yarwood, Richard
Abstract: Citizenship is gaining increased attention in the social sciences but has been under-utilised in rural studies. In this paper we argue that greater attention should be paid to social aspects of citizenship in order to understand participation in daily life and society. In doing so, emphasis needs to be placed on the rural citizen and how he or she engages with different communities across different scales. To explore these ideas we draw upon a case study of farmers living with dementia in Devon, UK. We use concepts of citizenship to explore their rights to services, the effectiveness of active citizenship policies and how the illness impacts on their life-worlds as farmers. We conclude by offering recommendations on the care of farmers with dementia and highlight the significance of citizenship to rural studies. Highlights: A focus on citizens, rather than citizenship, opens up new directions in rural studies. Dementia is an embodied, relational and socially-constructed illness that affects daily participation in society. Access to care services are problematic. Many farmers 'do not want to make a fuss' and need to be persuaded to use them. Formal community-based support is valuable but perceived changes in community make some farmers reluctant to engage with it. Informal networks of care are important; many farmers prefer to engage with peers outside their locality via social media.